Low temperature growth of carbon nanotubes on tetrahedral amorphous carbon using Fe–Cu catalyst. (January 2015) - Cartwright, R.; Esconjauregui, S.; Hardeman, D.; Bhardwaj, S.; Weatherup, R.; Guo, Y.; D'Arsié, L.; Bayer, B.; Kidambi, P.; Hofmann, S.; Wright, E.; Clarke, J.; et al.
Abstract: We report the growth of carbon nanotubes on tetrahedral-amorphous carbon using a Fe–Cu catalyst system at temperatures <500 °C. By X-ray photoemission spectroscopy, we show that Cu forms an alloy with Fe during the process of catalyst pretreatment. This not only dramatically enhances the catalytic activity of Fe towards the nucleation of nanotubes at low temperatures, but simultaneously reduces its propensity to diffuse into the bulk of carbon-based substrates, thus minimising support damage. Such results prove the feasibility of growing nanotubes directly on carbon fibres, highlighting their potential for use in composites and fuel cell electrodes.